Terrains of Imagination in Contemporary Finnish Literature - Kankkunen, Sarianna (Finnish Literature Society / SKS, 2025)
This study examines experienced space in Maarit Verronen’s works of prose fiction. The study aligns itself with the contemporary approach often referred to as spatial literary studies, a movement connected to the spatial turn within the humanities. Theoretically, the study draws on multiple fields of spatial studies, from semiotics of space to critical theory and poststructuralism. By providing a categorization on different approaches within spatial literary studies, the study promotes literary studies that utilize spatial theory and explores how spatial concepts can be effectively used as tools for close reading. Since the study aims to provide a longitudinal section of Verronen’s oeuvre, the selected material spans the author’s early works, from the 1990s to the late 2000s. The corpus involves six novels and two short stories. The analysis begins with the fantastic realms of Verronen’s early career, proceeds to consider wilderness and wild spaces, turns to visions of dystopic futures, and concludes in the narratives of homecoming and homesteading. The study shows that Verronen’s fantasy draws its allegorical potential from the juxtaposition of spatialized binary semantic oppositions. By analyzing Verronen’s dystopian novels, the study unravels the spatial nature of the genre and the critical potential it encompasses. Verronen’s narratives on wilderness are approached through the notion of spatial practices and in the context of alienation and postpastoralism. Finally, the analysis on the literary homes and the acts of homesteading in Verronen’s novels foregrounds the open, connected, and inclusive nature of the contemporary notion of home and new forms of attachment to place, both of which are under an active debate in spatial literary studies. By bringing together spatial literary studies and Verronen’s works, this research adds to the study of Finnish literature and contemporary literature’s emphasis on space, spatiality, and environmental issues. Moreover, the study contributes to the knowledge on the genres of fantasy and dystopia, as well as to the study of classic literary tropes and their contemporary manifestations. As the study contextualizes Verronen’s works within Nordic and European literatures, it draws attention to the thematic and stylistic connections that link her writing to broader literary trends and traditions.